PEMETAAN DERAJAT KEJENUHAN DAN KEBISINGAN PADA RUAS JALAN LEGUNDI HINGGA RUAS JALAN PRAMBON DI KABUPATEN SIDOARJO - Mohammad Malik Mulki; Hendrata Wibisana (LPPM Universitas Abdurrab, 2025)
Sidoarjo Regency is an area located in the south of Surabaya City with an area of ± 714.24 km², and a population of 2,091,930 people. Increased development and economic growth have caused congestion and noise problems in Sidoarjo Regency. This research was conducted with the aim of knowing the degree of saturation, noise value, and correlation value and mapping on Legundi Road to Prambon Road in Sidoarjo using a database in the form of a Geographic Information System (GIS). Data collection is done by direct survey to the research location using meter, traffic counter, and sound level meter. Based on the research results, it can be seen that there is congestion at several points on the research road with the highest DS value of 0.89 and the highest Leq value of 92.55 dBA. The correlation value of DJ with Leq is 0.366. Thematic mapping is done using ArcGIS application with point, polyline, polygon attributes.